Change in Adenosine Deaminase Serum Levels from Before and Six Months After Treatment in Patients with Tuberculous Lymphadenopathy - Christa Graziella Muljono; Soedarsono Soedarsono (Jurnal Respirasi, 2026)
Introduction: Tuberculous lymphadenopathy (TBLN) is challenging to both diagnose and treat. The outcome of a complete course of anti-tuberculosis (TB) drugs (ATDs) is evaluated based on clinical presentation and symptom improvement. Many clinicians administer ATDs for more than 6 months when they find residual lymphadenopathy or a paradoxical reaction. Therefore, this study assessed whether serum adenosine deaminase (ADA) levels are a suitable marker for evaluating the response to TBLN treatment and for analyzing changes in serum ADA levels from before to after 6 months of treatment with the standard ATD regimen in patients with TBLN. Methods: This prospective analytic observational study enrolled ATD-naïve patients with TBLN who received the standard 6-month ATD regimen in the TB directly observed therapy outpatient wards at Dr. Soetomo General Academic Hospital and Universitas Airlangga Hospital, Surabaya, from May 2023 to June 2024. Serum ADA levels were determined before and after treatment and compared using the Wilcoxon signed-rank test. Results: This study enrolled 22 patients, mostly female (n=14, 63.6%), with a mean age of 29.55±8.92 years old. The median serum ADA level was 18.7 (12.5-42.5) IU/L before and 13.9 (9.6-27.1) IU/L after treatment, with a significant mean decrease of -4.55 IU/L (p=0.001). Conclusion: Treatment with the standard 6-month ATD regimen decreased serum ADA levels in patients with TBLD. Therefore, serum ADA levels can be used as a follow-up test after treatment for patients with TBLN to evaluate their response to anti-TB therapy.